UV‐Cured Acrylic Conductive Inks for Microelectronic Devices. Issue 6 (6th August 2012) - Sangermano, Marco; Chiolerio, Alessandro; Marti, Giulio; Martino, Paola
Abstract UV‐curable inks based on a poly(ethylene glycol) diacrylate (PEGDA) matrix and containing a dispersion of aqueous Ag nanoparticles in different amounts from 10 to 50% are prepared for the fabrication of inkjet printed resistors. The composition is adapted to the inkjet requirements in terms of viscosity, surface tension, and particle size. The gel content, glass transition temperature, conversion, UV‐Vis absorption, morphology, and DC electrical properties of the materials are characterized. It is found that the NPs dispersed in the polymeric matrix realize a percolating path by aligning themselves in chains, which results in a reduction of the percolation threshold. Thus, resistivity is well beyond the dissipative range. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>